Exergoeconomic analysis and optimization of a novel integrated two power/cooling cogeneration system using zeotropic mixtures. (15th August 2022) - Mosaffa, A.H.; Garousi Farshi, L.
Abstract: This work deals with an exergoeconomic analysis for a new integrated power/cooling cogeneration system using zeotropic mixtures as working fluids with two levels of cooling temperature. The proposed system is comprised of two combined ejector refrigeration and power (CERP) cycles with different configurations using geothermal energy as the heat source. One subsystem is a conventional CERP system called basic subsystem and the other one is a CERP system employing a vapor-liquid separator called the bottoming subsystem. These subsystems are connected via a cascade heat exchanger in a parallel mode. The results of the parametric study show that geofluid mass fraction (that indicates the amounts of the mass flow rate of geofluid served thermal energy for basic and bottoming subsystems) has the biggest effect on the proposed system in comparison to other operating parameters. Furthermore, a multi-objective optimization with energy and exergy efficiencies and overall unit cost of products as objective functions is carried out for both basic and integrated CERP systems. The results of the comparison study for optimized systems show a significant performance improvement for the proposed system in comparison to the basic system. In this case, for the integrated CERP system, energy and exergy efficiencies increase by 3.88% and 4.76%, respectively, while the overall unit cost of products increases by 0.96 GJ −1, in comparison to the basic CERP system. Highlights: A conventional ejector refrigeration and power system using zeotropic is improved. An exergoeconomic analysis as well as comparative study is carries out. According to the parametric study, a good improvement is observed for proposed system. By conducting an optimization, an increase of 4.76% is observed in exergy efficiency.